Help-seeking for Intimate Partner Violence and Abuse: Experiences of Serving and Ex-serving UK Military Personnel - Lane, Rebecca (Journal of family violence, 2024)
PurposeIntimate Partner Violence and Abuse (IPVA) is as a major health concern globally. The prevalence of IPVA perpetration and victimisation has been found to be higher in military compared to civilian populations. Of concern, help-seeking for other psychosocial difficulties among military communities has been shown to be both limited and challenging, and military personnel could face additional or amplified barriers to help-seeking for IPVA than their civilian counterparts. This study aimed to use qualitative methods to explore the experiences of, and barriers to, help-seeking for IPVA victimisation and perpetration among UK military personnel.MethodsThematic analysis was conducted on 40 one-to-one semi-structured interviews with military personnel (29 male, 11 female).ResultsFour superordinate themes were derived, thematically organised according to different levels of the social ecological model: Military cultural factors; Support service factors; Interpersonal factors; and Individual factors. At a military cultural level, participants described difficulties in help-seeking for IPVA resulting from widespread stigma and hypermasculine attitudes in military communities, minimisation of violence, perceived pressure from chain of command, and fear of consequences of reporting. At a support-service level, participants’ negative views or experiences and lack of awareness of services were also significant in deterring help-seeking. At an interpersonal level, participants recounted how relationships with military colleagues, their partner and their family could be both instrumental or a hindrance to help-seeking for IPVA. At an individual level, lack of insight into IPVA and different forms of abuse were suggested through minimisation of violence and described to contribute to delay in help-seeking. Shame, compounded by multi-layered stigma present at each social ecological model level, was a key reason for delaying or avoiding help-seeking.ConclusionsThe findings indicate the added challenges in help-seeking for IPVA experienced by military personnel and highlight a need for a whole systems approach to improve the provision of support for IPVA in the military serving and ex-serving community to instil meaningful change.